Mozart's The magic flute - Schikaneder, Emanuel, 1751-1812 (Opera classics library., 2005)
A comprehensive guide to Mozart's THE MAGIC FLUTE, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with German/English translation side-by side, and over 30 music highlight examples.